Constraints on Trade in the MENA region - Wolde, Hirut (IMF Working Papers; Working Paper ;, 2010)
In this paper we estimate gravity models to see whether trade volumes of countries in the MENA region are significantly lower than what would be expected given their economic, cultural and geographical characteristics. Our empirical results show that the variables used in standard gravity models cannot explain a significant part of MENA's trade performance, particularly on exports. We then go on to 'augment' the standard gravity model with relevant variables from the World Bank's Business Enterprise surveys. Our results further show that these variables, and in particular transport constraints and inefficiencies in customs clearance processes, are important in explaining the MENA region's underperformance in trade.